UTILIZING A WEB-BASED LEARNING MEDIUM IN ELT: HOW STUDENTS PERCEIVED WEBQUEST IN PROMOTING ENGLISH SKILLS - Ira Irzawati (Jurnal Didascein Bahasa, 2017)
The utilization of web-based learning media in English Language Teaching (ELT) has become a popular trend and gained more acceptances among educators and students in recent decades. Webquest is a web-based learning medium used for supporting students in learning and improving their English skills. The aims of this study was to find out whether Webquest can be an alternative learning medium for students to promote the enhancement of their English skills, especially reading and writing through investigating the way students perceived it in teaching and learning process. This study used descriptive method which involved thirty-one of eleventh grade students as the participants. The data were collected by conducing interview and administering questionnaire dealing with five issues; instruction and timing, task, relevance and involvement, collaborative learning, and evaluation. The result revealed that students had favorable perceptions towards the use of Webquest in promoting their reading and writing skills. The students believed that Webquest is an alternative learning medium which facilitate them to attain deeper comprehension and better achievement both in reading and writing. Keywords: Webquest, learning, perception, reading, writing.